Қорғасын ацетатын50 мг/кг мөлшерде10 тəулік бойы құрсақ ішіне енгізгенде тышқандарда жілік майының кемігінде миелосупрессияның дамуына алып келді. 3 күн аралығында пайда болған иммундыдепрессивті синдромды БИВ-7 қосылысын енгізгенде жілік майының клеткалы (Experimental biology, 2015)
Intra-peritoneal injection of acetate of lead in a doze of 50 mg/kg after 10 day has led the development the myelosupression of bone marrow pool at mice. On the background got immunodepresive syndrome the treatment lead during 3 days by azageterocycle chemical substance BIV – 7 has authentically accelerated regeneration neutrophyle, lymphocyte and monocyte cells pull of bone marrow. So the study has shown hemostimulated activity of chemical substance BIV – 7 on the model of bone marrow hemopoiesis deficiency.